Landscape approach to implement sustainability policies? - Richnau, Gustav (2008)
Southern Sweden's forest and cultural woodland landscapes provide natural resources in terms of goods, services and values to a wide range of actors and stakeholders. In this survey value profiles among different forest owner categories in the Helgeå river basin in southern Sweden were explored. The study area encompassed 14 different municipalities and a total area of 11 336 sq. km. Products derived from the forest land were divided into use values and non-use values. Direct use values included (1) consumptive (e.g., timber and non-timber forest products) as well as (2) non-consumptive use values (e.g., landscape quality or recreation). Indirect use values included ecosystem services such as soil and watershed protection. Non-use values were closely linked to environmental and cultural conservation interests. A total of 89 telephone interviews were conducted in late 2007 with non-industrial private forest owners and forest managers or representatives of fourteen municipalities, the Swedish environmental protection agency, the Church of Sweden and the state owned forest company Sveaskog Co. The value profiles of small-scale private land owners and municipalities were very broad. The primary objective of the Church of Sweden and Sveaskog Co. was centred on wood production, while the Swedish environmental protection agency focused on environmental protection issues. Finally, the ambitions of current sustainable forest landscape policies were compared with the observed state and trends of the economic, ecological, social and cultural aspects of the sustainability concept. While the economic dimension appears to be satisfactory fulfilled, there seems to be a need for landscape and regional level approaches for governance and management to satisfy ecological, social and cultural aspects. Landscape approaches such as Model Forest and Biosphere Reserve thus appear to be relevant tools.